Functional silicon nanostructures derived from drying-mediated self-assembly of gold nanoparticles - Deshmukh, Ashvini B.; Devarapalli, Rami Reddy; Shelke, Manjusha V. (Journal of Nanoparticle Research, 2014)
Self-assembly of nanoparticles is an efficient technique where nanobuilding blocks spontaneously organize into ordered structures by thermodynamic and other constraints. We demonstrate that multifunctional Silicon (Si) nanostructures with unique morphologies like sheets, plates and flakes can be etched chemically by taking an advantage of natural self-assembly of gold nanoparticles (AuNPs) characterized with drying kinetics under external stimuli. We further demonstrated antireflection properties of the as-synthesized Si nanostructures.
Keywords: Antireflective material; gold nanoparticles; Metal-assisted chemical etching; Self-assembly; Si Nanostructures